2000
DOI: 10.1152/jn.2000.83.1.501
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of Odor-Induced Ca2+ Transients by Store-Operated Ca2+ Release and Its Role in Olfactory Signal Transduction

Abstract: release does not seem to be necessary for generation of an immediate electrophysiological response, nor does it contribute significantly to the Ca 2ϩ transients in the olfactory cilia. Rather, it is important for amplifying the magnitude and duration of Ca 2ϩ transients in the dendrite and soma and is thus necessary for the spread of an odorinduced Ca 2ϩ wave from the cilia to the soma. We show that this amplification process depends on Ca 2ϩ -induced Ca 2ϩ release. The results indicate that stimulation of ORN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 64 publications
(70 reference statements)
2
41
0
1
Order By: Relevance
“…That SST 3 activation is required for full stimulation of AC by forskolin, a direct activator of AC, suggests the receptor may be acting upstream of ACIII, perhaps blocking an inhibitory constraint such as CaM kinase II, a well established inhibitor of ACIII (Wei et al, 1996). Alternatively, activation of ACIII could generate a Ca 2ϩ transient that is transmitted to and amplified in the neuronal soma, as in olfactory cilia (Zufall et al, 2000). This could activate Ca 2ϩ -dependent ACs such as ACI and ACVIII, leading to a secondary wave of cAMP.…”
Section: Discussionmentioning
confidence: 99%
“…That SST 3 activation is required for full stimulation of AC by forskolin, a direct activator of AC, suggests the receptor may be acting upstream of ACIII, perhaps blocking an inhibitory constraint such as CaM kinase II, a well established inhibitor of ACIII (Wei et al, 1996). Alternatively, activation of ACIII could generate a Ca 2ϩ transient that is transmitted to and amplified in the neuronal soma, as in olfactory cilia (Zufall et al, 2000). This could activate Ca 2ϩ -dependent ACs such as ACI and ACVIII, leading to a secondary wave of cAMP.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular calcium levels can also increase over larger spatial and temporal scales. This amplification, often through release from intracellular stores (Jaffe and Brown, 1994;Nishiyama et al, 2000;Zufall et al, 2000), can affect cellular processes such as gene expression (West et al, 2001; W. G. that contribute to more persistent synaptic plasticity (Chen W. G. et al, 2003). Thus, it is of interest to visualize intracellular calcium dynamics within a neuron while it undergoes induction and expression of synaptic plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…This Ca 2ϩ influx does not depend either on the reverse operation of the Na ϩ /Ca 2ϩ exchanger (DiPolo and Beauge 1987) because we found that its blockage resulted in an increase in the amplitude and duration of the Ca 2ϩ transients. Thus this exchanger probably participates in restoring basal [Ca 2ϩ ] i as has been reported for other neurons (Fierro et al 1998), including ORNs (Jung et al 1994Noe et al 1997;Reisert and Matthews 1998;Zufall et al 2000). Because we found that both ESS and BK responses seem to depend on IP 3 production, it appears likely that this Ca 2ϩ influx depends on activation of an IP 3 conductance in VN dendritic membranes.…”
Section: Component Of Ess Response Dependent On Ca 2ϩ Influxmentioning
confidence: 54%
“…This result differs from otherwise similar Ca 2ϩ signals associated with chemosensory transduction in mouse VN neurons and in ORNs (Leinders-Zufall et al 1997;Restrepo et al 1990Restrepo et al , 1993Sato et al 1991;Schild et al 1995;Tareilus et al 1995), which are completely suppressed in 0 [Ca 2ϩ ] o . It is interesting to note that Ca 2ϩ release from internal Ca 2ϩ pools also occurs in ORNs, but this mechanism appears to be secondary to an initial Ca 2ϩ influx that is mediated through the opening CNG channels (Leinders-Zufall et al 1998;Zufall et al 2000).…”
Section: Component Of Ess Response Dependent On a Ca 2ϩ Releasementioning
confidence: 99%